2010
DOI: 10.1021/jo101305m
|View full text |Cite
|
Sign up to set email alerts
|

Chelation-Assisted, Copper(II)-Acetate-Accelerated Azide−Alkyne Cycloaddition

Abstract: We described in a previous communication (ref. 13) a variant of the popular Cu I -catalyzed azidealkyne cycloaddition (AAC) process where 5 mol% Cu(OAc) 2 in the absence of any added reducing agent is sufficient to enable the reaction. 2-Picolylazide (1) and 2-azidomethylquinoline (2) were found to be by far the most reactive carbon azide substrates that convert to 1,2,3-triazoles in as short as a few minutes under the discovered conditions. We hypothesized that the abilities of 1 and 2 to chelate Cu II contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
120
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(124 citation statements)
references
References 34 publications
4
120
0
Order By: Relevance
“…Kuang et al reported non-reductive conditions using Cu(OAc) 2 and by chelating the azides with Ncontaining auxiliary ligands to increase significantly the rate of the reaction. 13 CuAAC one-pot synthesis of 5-iodo-1,2,3-triazoles was also described. 14,15 In the case of the regioselectivity towards 1,5-disubstituted-triazoles, ruthenium catalysts (RuACC) were the most commonly used for both thermal 7 or microwave 16 conditions, which also support internal alkynes.…”
Section: Generalitymentioning
confidence: 99%
“…Kuang et al reported non-reductive conditions using Cu(OAc) 2 and by chelating the azides with Ncontaining auxiliary ligands to increase significantly the rate of the reaction. 13 CuAAC one-pot synthesis of 5-iodo-1,2,3-triazoles was also described. 14,15 In the case of the regioselectivity towards 1,5-disubstituted-triazoles, ruthenium catalysts (RuACC) were the most commonly used for both thermal 7 or microwave 16 conditions, which also support internal alkynes.…”
Section: Generalitymentioning
confidence: 99%
“…Those azides, which are termed "chelating azides," contain auxiliary ligands capable of assisting the azido group in binding the copper centre. [9] To expand the substrate scope of the Cu-A C H T U N G T R E N N U N G (OAc) 2 -mediated procedure to include nonchelating azides, we investigated conditions that employ an accelerating ligand.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19] We recently found that TBTA also accelerates CuA C H T U N G T R E N N U N G (OAc) 2 -mediated AAC reactions that involve nonchelating azides. [9] In a number of reactions that proceed sluggishly under Cu-A C H T U N G T R E N N U N G (OAc) 2 -mediated conditions, yields of over 90 % were achieved in the presence of TBTA within 1 or 2 h. In this work, we investigated the acceleratory effects of other polytriazoles in CuA C H T U N G T R E N N U N G (OAc) 2 -mediated AAC reactions. The kinetic studies were also carried out to provide some insights on the mechanistic involvement of TBTA (as an example of polytriazole ligands) under the CuA C H T U N G T R E N N U N G (OAc) 2 -mediated conditions.…”
Section: Introductionmentioning
confidence: 99%
“…42 Pyridine containing azides were particularly reactive in CuAAC in the presence of Cu(OAc) 2 /t-BuOH, 43 although amine, carboxylic acid, ether and thioether groups also increased the reaction rates.…”
Section: Amine Ligandsmentioning
confidence: 98%